City Silhouette, World Climate - Kristof Dascher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
A country's urban silhouettes prophesy its future climate policy, or so this paper argues. The more its city silhouettes are skewed to the periphery, the more likely a country is to implement the carbon tax. This is why the effect of a country's urban form on greenhouse gas emissions – a bone of contention in the recent literature – cannot be separated from that country's choice of carbon tax. From this paper's perspective, a country with greater city silhouette skews may emit less greenhouse gases not so much because its cities are more compact but because it places a higher price on carbon consumption.
Keywords: R12; Q54; H41; 330